2013
DOI: 10.2174/15748898112079990016
|View full text |Cite
|
Sign up to set email alerts
|

Different Classes of CB2 Ligands Potentially Useful in the Treatment of Pain

Abstract: The search of new drugs and targets to treat the pain is an intriguing challenge both for several companies and researchers from academia. In this context, since the modulation of the endocannabinoid system with the non selective phytocannabinoid Δ9-THC produces analgesia and potentiates opioid analgesia in animal models, CB2 ligands studies aimed to explore the involvement of endocannabinoid system in management of pain were started. Several selective CB2 receptor agonists exhibited analgesic activity in prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…These findings offered the possibility of producing significant analgesia through the endogenous cannabinoid system in the absence of CB 1 -mediated psychoactivity. Subsequent work by a number of groups has confirmed and extended these studies with a variety of structurally distinct CB 2 agonists (Murineddu et al, 2013). Generally, the field has moved away from AM1241, as AM1241 appears to engage a unique endogenous opioid-mediated component for its analgesia (Ibrahim et al, 2005;Whiteside et al, 2005); its enantiomers have different actions and its efficacy is species-dependent (Bingham et al, 2007); and it is a low-efficacy agonist, as it exhibits protean agonism (Yao et al, 2006).…”
Section: Preclinical Studies Of Cb 2 Agonists In Painmentioning
confidence: 99%
“…These findings offered the possibility of producing significant analgesia through the endogenous cannabinoid system in the absence of CB 1 -mediated psychoactivity. Subsequent work by a number of groups has confirmed and extended these studies with a variety of structurally distinct CB 2 agonists (Murineddu et al, 2013). Generally, the field has moved away from AM1241, as AM1241 appears to engage a unique endogenous opioid-mediated component for its analgesia (Ibrahim et al, 2005;Whiteside et al, 2005); its enantiomers have different actions and its efficacy is species-dependent (Bingham et al, 2007); and it is a low-efficacy agonist, as it exhibits protean agonism (Yao et al, 2006).…”
Section: Preclinical Studies Of Cb 2 Agonists In Painmentioning
confidence: 99%
“…Thus, recent studies have revealed that non selective cannabinoid agonists reduce the cognitive impairment associated to diabetic neuropathy [24] and selective CB2R agonists reduced the depressive-like behavior [43] and alleviate spontaneous neuropathic pain in an operant model of selfmedication [39]. Interestingly, these CB2R agonists are devoid of the cannabimimetic effects of CB1R agonists [74].…”
Section: Preclinical Studies On Endocannabinoid System and Neuropathic Painmentioning
confidence: 99%
“…New strategies for using cannabinoids more efficiently include the selective targeting of CB1R and CB2R, the inhibition of endogenous cannabinoid uptake and metabolism in selected tissues, the harnessing of cannabinoid-opioid synergies, and the delivery of cannabinoids by improved strategies [118]. Indeed, several selective CB2R agonists and MAGL/FAAH inhibitors have shown promising analgesic activity in preclinical models of neuropathic pain [46,74]. However, these promising results must be confirmed in more relevant animal models of neuropathic pain with experimental conditions closer to the clinical conditions.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Although both CB1 and CB2 receptors have been detected in leukocyte mediators of inflammation, CB2 is believed to play a more important role and appears to be the key mediator of cannabinoid regulation of inflammation and immune functions. CB2R is primarily expressed in peripheral organs and especially in immune cells [ 2 , 3 ]: compared to CB1R, it shows 10- to 100-fold higher expression in cells of the immune system such as B and T lymphocytes, monocytes, and macrophages [4] . CB2R plays an important role in regulating inflammatory responses under both physiological and pathological conditions, and small-molecule modulators of CB2R including agonists have been developed for the treatment of various inflammatory diseases [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%